(3GdYdd hGdCYQGV dLGdjfhSs - (3LGdjfhSs
(3ChdgG (B:s
(3Ef Ghd eG jfHZi dfG Cf fPcQg , eG GdTF GdPi fSejg eQVkG cjeG fYde eG ZQV gPg GdebGdI , hEdi Ci TF jbUO HgG? hGdKGfi HYO gPG (B: s
(3BNQgG (B:s
(3hYdi gPG GdeKGd jecfc Gf JSJNQL aj LejY CLfGS GdCYQGV CjgG jJHY HYVgG HYVkG , hCjgG dGjJHY OGFekG hCeG CfG adTabJi Ydi afGA GdhbJ HGdJWhjd QCjJ Gf CbWY GdcdGe gfG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfjs
(3GfXQ agQS GdWH HQbe (B164s
(3fSNI KGfjIs
(3hgh aj GdCTjGA GdNGQLI Yf GdWHjYIs
(3LYdg LGdjfhS aj SJ ebGdGJ oeJaQbI s
(3hEfeG LeYgG GdEScfOQGfjhf hLYdhgG cJGHkG hGMOkG s
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdWHs